Uma proposta de integração curricular entre o ensino de física e o tema solos no curso técnico em meio ambiente do instituto federal do amapá – campus Laranjal do Jari - ALMEIDA, Willians Lopes de (2016)
The concepts and laws of physics are widely used in research aimed at improving environmental quality, providing theoretical bases / practical solution to the problems of the environmental pollution. Such problems are made up of various aspects ranging from contamination of water, air and soil, to landscape changes. On the ground, this is not just a piece of ground; it is very complex and consists of several elements such as organic matter, water, air and especially life. Considering the importance that the study of soil has been the need to bring this knowledge to the basic cycle of education, in order to wake up early on the aspects of the practice of conscious use of this ecosystem element. Given this, it is clear that there is a range of possibilities to work with the subject in the school context, given its importance, ease of viewing changes resulting from the misuse or disorderly occupation of land and also its transdisciplinary character. One such possibility is the soil resistivity of the study, which harnesses knowledge of physics, as well as composition and soil contamination. Many students question the importance of studying physics considering that this curriculum component will not be useful to you in your everyday life or professional activities. In this perspective, thinking teaching strategies that engage students in both their educational background as a professional in order to make them recognize the role of science in the transformation of society, it is the role that the teacher has and his commitment to each education better. Thus, with the support of the theory of meaningful learning, could be assessed, opposite the existing transdisciplinary relationship between physical and thematic soil, through the study of soil electrical resistivity in a low cost experiment, recognition and learning more dynamically and satisfactory. Based on the results it can be said that the transdisciplinary proposal, through experimentation, from the concept of electrical resistivity as curriculum integration component between physics and soil, was successful, given the good evaluation that students employed in job. The role of experimentation in the teaching-learning process in physical education, in this context, reflected in improvements in student learning and made them recognize the relationships between the two curriculum components: physical and soils. The methodological strategy used in this study contributed to the characterization of vocational training in the technical environment and this allowed the study subjects were able to understand the content taught in a more meaningful way. The results obtained in the post-test and evaluation of the work by the students, it was found that they have recognized the significance of the concept of soil electrical resistivity and experienced a significant learning, given all the context that passed during the execution of this research.